PENERAPAN PEMBELAJARAN BERBASIS PROYEK (PJBL) DALAM MENINGKATKAN KREATIVITAS SISWA PADA PEMBELAJARAN IPAS KELAS V SDN 14 BANDA ACEH - Dinda Fitria; Ahmad Nasriadi; Teuku Mahmud (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Natural and Social Sciences (IPAS) learning in elementary schools plays a very important role in developing students’ logical, critical, and creative thinking skills in understanding various natural and social phenomena occurring in their surrounding environment. However, in its implementation at the elementary school level, various problems are still found, particularly related to the low level of students’ creativity during IPAS learning. This study aims to analyze the effect of implementing the Project-Based Learning model on improving students’ creativity in IPAS learning for Grade V at SDN 14 Banda Aceh, as well as to describe the level of students’ creativity after the implementation of the learning model. This research employed a quantitative approach using an experimental method with a One Group Pre-test–Post-test Design. The research subjects involved all 22 students of Grade V A at SDN 14 Banda Aceh. Data were collected through a creativity test administered before the treatment (pretest) and after the treatment (posttest). The obtained data were then analyzed using the Paired Sample t-Test, preceded by prerequisite tests in the form of normality and homogeneity tests. The results of the data analysis using statistical software showed a significance value of 0.000 (p < 0.05), indicating that the alternative hypothesis was accepted and the null hypothesis was rejected. Therefore, it can be concluded that the implementation of the Project-Based Learning model has a significant effect on improving students’ creativity in IPAS learning for Grade V at SDN 14 Banda Aceh